A STUDY ON THE DEVELOPMENT OF PROFESSIONAL COMPETENCE IN FUTURE ENGLISH LANGUAGE TEACHERS (Educa Journal of Studies, 2026)
The growing role of English as a global means of communication has increased the demand for highly qualified English language teachers. This paper examines how professional competence develops among future English teachers and why it is essential in modern education. The study is based on the analysis of theoretical sources, educational practices, and current trends in language teaching. The findings show that effective teaching depends on a combination of linguistic knowledge, pedagogical skills, technological awareness, and the ability to reflect on one’s own practice. The paper argues that teacher education programs must focus on developing these competencies in an integrated way to prepare teachers for real classroom challenges.
Keywords: Professional competence, English language teaching, teacher education, communicative competence, pedagogy, digital skills.